An Empirical Study of Food Safety, Food Handling, and Food Poisoning Awareness Among Foreign Students in Penang, Malaysia - Mahmood, Kaiser; Khalid, Jamshed; Kamilah, Hanisah; Ali, Anees Janee; Muhammad, Lubowa; Ariffin, Fazilah (International Journal on Advanced Science, Engineering and Information Technology, 2018)
These foreign students are highly concerned with food safety and food handling knowledge as they are presumably involved in perilous eating behaviours, which exposes them to the risk of foodborne diseases. The present cross-sectional study aimed to evaluate the awareness and practices regarding food safety and food handling among the foreign students of Universiti Sains Malaysia (USM), Penang. A self-administered questionnaire was used to collect demographic information and to assess awareness of food safety and food handling among foreign students. Questionnaires were distributed into five sections that concealed key food safety apprehensions. A total of 328 students received the questionnaires, and 203 (61.89%) responded. Cleanliness of eating tables, food temperature, smoke-free environment and food handler appearance are the key food safety considerations for the respondents. The results showed that a high percentage of male respondents (57.98%) experienced food poisoning, and considered food from restaurants is the cause of foodborne diseases. Respondents have utmost awareness about the cleanliness of utensils and kitchen surfaces, hand hygiene, and preclusion of cross-contamination, however, described a poor knowledge concerning the temperature and heat treatment of the food. Good understanding regarding food poisoning symptoms was observed among the respondents, especially in a female group. The outcome revealed that foreign students, irrespective of gender, demonstrated comparable food safety and food handling knowledge. The study laid emphasis on education and training as an optimum way to foster awareness and encourage students’ food safety knowledge and practices.